Nickel-induced enhancement of photoluminescence in nc-Si–SiOx nanostructures - Michailovska, K.V.; Indutnyi, I.Z.; Shepeliavyi, P.E.; Dan’ko, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The effect of nickel silicide interlayer on the intensity of photoluminescence (PL) from Si nanoclusters (nc) in normally deposited and obliquely deposited in vacuum SiOx/Ni/Si structures have been studied using spectral and time-resolved PL measurements. It has been shown that the intensity of PL band in SiOx/Ni/Si samples is essentially higher than that in reference SiOx/Si samples (without the nickel interlayer) with the same characteristics and treatment. The PL intensity enhancement factor is equal to 5.77 for normally deposited samples and 18 for obliquely deposited samples. The unchanged spectral shape of PL bands and similar position of PL maximum in samples with and without nickel silicide interlayer indicates that in the SiOx/Ni/Si structures after annealing no additional emitting centers are introduced to compare with reference one. Time-resolved measurements showed that PL decay rate was decreased from 8.2*10⁴ s⁻¹ for SiOx/Si specimens to 2.86*10⁴ s⁻¹ for SiOx/Ni/Si one. The emission decay rate distribution was determined by fitting the experimental decay curves to the stretchedexponential model. The observed narrow decay rate distribution, decrease of the PL decay rate and enhancement of the PL intensity in SiOx/Ni/Si samples can be assigned to the processes of nickel silicide passivation of the dangling bonds at the interface of Si nanoparticles and the silicon oxide matrix, which is more effective in porous samples.